As ativistas maranhenses e a redemocratização do Brasil: gênero, sexualidade e contracultura na Ilha de São Luís (1980-2010) - MOITA, Júlia Francisca Gomes Simões (2024)
In the 1970s, the left-wing in São Luís begin a time of intense mobilizations demanding democracy and freedom for the country. The feminist, black and environmental movements are increasingly present in the city and bring new approaches to historical struggles issues in the state. The first feminist movement, Mulheres da Ilha, uses news political meanings, challenging behavior and building ways of popular participation. This democratics mechanisms are important for the LGBT+ movement, which was established in Maranhão, in the late 1990s. Before the formal political organization of LGBT+, however, there was already a circulation of LGBT+ subjects throughout the capital, foreshadowing the creation of the Grupo Lésbico do Estado do Maranhão. I spoke with activists and, based on these memories, I recreate the atmosphere of São Luís in the period considering the emergence of gender and sexuality policies on the Island.